ANALYSIS OF INVESTMENT OF THE CULTIVATION SYSTEM OF PRE-GERMINATED RICE COMPARED TO THE CONVENTIONAL CULTIVATION: A CASE STUDY IN THE CENTRAL LOWLANDS OF THE STATE OF RIO GRANDE DO SUL - Porporatti Arbage, Alessandro (2014)
The objective of the present work was to analyse the necessary investment to alter the conventional production system of irrigated rice to the pre-germinated rice in a rural property located in the Central Lowlands of the State of Rio Grande do Sul, Brazil. The main rentability indicators recommended by the financial theory such as the net present value and the payback with and without discount. The adopted methodology in this work was the analysis of the differential cash flow between the cultivation system of pre-germinated rice and the conventional one. The necessary investment for the establishment of the pre-germinated rice were estimated and the differentiated cash flow for a period of 10 years was analysed. The results indicate that the pre-germinated system is effectively more efficient in relation to costs and revenue, since they gave a positive Net Present Value (R$26,572.77), an Internal Tax Return of 22% and the Payback with discount was 6.11 years.